Efektivitas Model Pembelajaran SSCS (Search, Solve, Create, and Share) dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis - Anas Anshori; Masriyah Masriyah (MATHEdunesa, 2023)
The ability to solve mathematical problems is an important ability that must be possessed by students, one of its functions is to be able to find solutions to mathematical problems. The purpose of this study was to examine the effectiveness of the SSCS learning model in improving students' mathematical problem solving skills. This research is a descriptive research with a mixed methods approach. The subjects in this study were students of class X SMAN 1 Ngadiluwih. The instruments used were observation sheet of teacher's ability to manage SSCS learning, student activity observation sheet, pretest-posttest sheet, and student response questionnaire sheet. Based on the analysis, it was obtained that the teacher's ability to manage SSCS learning was included in the good category, student activities that met the criteria for learning effectiveness were only 3 out of 7 activities, the n-gain score obtained was 0.33, and learner responses were positive. Based on the analysis of research data, obtained: 1) The teacher's ability to manage SSCS learning is included in the effective criteria. 2) Learners' activities are included in the ineffective criteria. 3) Problem solving ability of students shows an increase. 4) Learners gave a positive response to the application of the SSCS learning model. From the description above, it can be concluded that the SSCS learning model in improving mathematical problem solving skills is not effective if applied to distance material in space in class X3 SMAN 1 Ngadiluwih.